Promotion of Renewable Energy Sources in the European Union - Menges, Roland; Pfaffenberger, Wolfgang (International Journal of Renewable Energy Development, 2015)
One of the important goals of European energy policy is to increase the share of renewable energy resources in the energy supply. The instruments used in the member states are not fully compatible with the rules of the European internal market. In a theoretical section, this paper analyses possible different instruments for promoting renewable energy. Some countries use feed in tariffs - using fixed prices to increase incentives for producers to invest into renewable energy, other countries use quantity-based systems like quotas that lead to a premium above the market price. In an institutional analysis we show that on the basis of effectiveness and efficiency considerations for the European Union, in the long-term quantity oriented systems of promotion are preferable if combined with elements of a capacity market. The main reason for this conclusion is that price-based systems cannot give enough incentives for backup capacities necessary to cope with intermittent production of renewable sources. In addition price-based systems violate the basic rules of the open internal European market because feed in tariffs are a considerable barrier for trade of renewable energy products.